LITERASI ASURANSI SYARIAH SAAT KONGRES MUSLIMAT NAHDATUL ULAMA DI SURABAYA - R Melda Maesarach (Taksasila Edukasi Insani, 2025)
Islamic financial literacy, particularly in Sharia insurance, remains relatively low in Indonesia, including among members of Muslimat Nahdlatul Ulama (NU). Sharia insurance plays a crucial role in providing financial protection based on Islamic principles, eliminating elements of gharar (uncertainty), maysir (speculation), and riba (usury), which are commonly found in conventional insurance. This community service program aimed to enhance the understanding and awareness of Muslimat NU members regarding the concepts, benefits, and mechanisms of Sharia insurance through a financial literacy lecture held as part of the 18th Muslimat NU Congress, conducted on Friday, February 14, 2025, in Surabaya, Indonesia. The program was implemented in the form of an interactive lecture, covering the fundamental differences between conventional and Sharia insurance, the principles of ta’awun (mutual assistance) and takaful (joint responsibility) in Sharia insurance, and the Indonesian National Sharia Board (DSN-MUI) fatwas on insurance and the waqf of insurance benefits. Additionally, a discussion and QA session allowed participants to clarify their understanding and explore the practical applications of Sharia insurance in their daily lives. The results of the program indicate a significant increase in participants' understanding of Sharia insurance, as many who were previously unfamiliar with the concept became aware of the importance of Sharia-based financial protection. As a follow-up, it is recommended that similar educational initiatives be conducted continuously, through collaborations between Muslimat NU, Sharia financial institutions, and regulatory bodies, while also utilizing digital platforms to expand public access to Sharia financial literacy. With improved knowledge and awareness of Sharia insurance, more Muslims will be able to access financial protection that aligns with Islamic values, contributing to the empowerment and sustainable economic development of the Muslim community.Keywords: Sharia Insurance, Financial Literacy, Muslimat NU, Community Service, Islamic Economics